Variations in levels of selected micronutrients during malaria infection: A study from Ado-Ekiti, Ekiti, Nigeria - Oluboyo, A.O.; Fakologbon, O.D.; Oluboyo, B.O.; Odewusi, O.O.; Ajayi, F.O. (Journal of Biomedical Sciences, 2018)
Background Malaria infection has been a global issue most especially in tropical and subtropical regions. Disease progression to severe malaria as a result of alteration in micronutrients could worsen the illness. The study aimed to determine whether there are variations in the levels of selected micronutrients (Iron, copper, magnesium, and zinc), malaria parasite density and packed cell volume (PCV) during malaria infection.Material and methods A total of one hundred young adults between the ages of eighteen and twenty two years were investigated. Blood samples were collected from fifty malaria subjects and fifty apparently non-infected subjects. Malaria detection was by microscopy while the parasite density was estimated using WHO standard procedure. Analysis of selected micronutrients (copper, iron, magnesium and zinc) was carried out using direct measurement on atomic absorption spectrophotometer and PCV was estimated using Micro-haematocrit method.Results The results showed that the levels of the micronutrients were significantly higher (p